Impact of E-Service Quality in Customer E-Loyalty of Marketplace with the Role of E-Satisfaction as Mediation - Gilang Pratama Hafidz; Muhamad Khaidir Ali (Jurnal Indonesia Sosial Teknologi, 2024)
In the e-commerce sector, attaining customer loyalty is a formidable task that necessitates particular focus from firms to outdo their contenders. This study sought to comprehensively comprehend the impact of e-service quality (e-SQ), encompassing seven utilitarian and two hedonic aspects, on customer e-loyalty in the marketplace. Both e-satisfaction and perceived value were examined as moderators and mediators, respectively, to provide a more empirical perspective. The study distributed online questionnaires to 265 participants between the ages of 18 and 60 who made at least two purchases from the top five Indonesian marketplaces within the last three months and reside in Greater Jakarta (Jabodetabek). The collected data underwent analysis using Structural Equation Modeling - Partial Least Square (SEM-PLS). The findings indicated that e-S) has the potential to enhance customer e-satisfaction. Similarly, e-SQ can enhance customer loyalty both directly and indirectly by in-creasing e-satisfaction. Additionally, customer satisfaction with the electronic plat-form has a positive impact on e-loyalty. Notably, perceived value does not play a moderating role in the influence of both factors. This study indicates that businesses operating in the e-commerce sector could enhance e-SQ factors like enjoyment, system availability, fulfillment, and efficiency to maximize e-satisfaction and e-loyalty.